The Brazilian Army and The Political Instrumentalization of Memory - Fernanda R. Abreu Silva (Confluenze)
The involvement of high-ranking military personnel in Brazil's politics has become common, especially after Jair Bolsonaro's election as a former army captain. Their political statements often reference the 1960s-1980s authoritarian military regime, keeping the dictatorship's memory alive in debates. Using sources like the Military Club Magazine, this article explores the Brazilian Army's narrative on the dictatorship, the movement to preserve its memory, and its political use by officers outside military headquarters in the past decade.